Dental Arch Development of Chinese Adolescents: A Retrospective Cross-Sectional Study - Chao Liu; Jieyi Chen; Mengjuan Cui; Zhengliang Wang; Wentao Shi; Siyuan Du; Yang Feng; Manfei Zhang; Zhenxia Li; Shufei Ge; Bing Fang (International Dental Journal)
Introduction and aims: Understanding the patterns of dental arch development is crucial for precise diagnosis and management of malocclusion in adolescents. However, large-scale, region-specific analyses based on big data are scarce.This study aimed to identify the dental arch growth patterns of Chinese adolescents to refine early orthodontic treatment strategies. Methods: A retrospective cross-sectional analysis was conducted using 3D digital impressions from 5951 Chinese adolescents, collected between July 2020 and June 2021. AI-assisted measurements delineated dental arch dimensions, which were analyzed using locally weighted regression to chart developmental trends and Lasso regression to explore influencing factors, with a particular focus on geographical variances. Results: Significant differences in dental arch dimensions were observed between genders and across different latitudes. Males generally displayed larger arch dimensions than females of the same age. The dental arches experienced rapid growth before age 13.7 in males and 13.1 in females, with limited growth potential in later years, with regional disparities evident in the magnitude of dental arch dimensions. These variations were prominently associated with geographical latitude, underscoring the influence of environmental factors on dental arch development. Conclusion: This comprehensive study provides valuable regional insights into the dental arch development of Chinese adolescents, facilitated by advanced AI methodologies. The fitted curves of age-specific dental arch offer valuable insights for optimizing early orthodontic treatment strategies. The findings advocate for region-tailored orthodontic planning and highlight the potential of AI in enhancing the precision of orthodontic treatment. Clinical Relevance: Our study of 5951 3D dental models reveals gender and geographical differences in arch growth, highlighting pre-teen rapid growth and later limitations, informing treatment planning.